Effect of supplementation of concentrate mixture or barley grain to grazing goats on nutrient utilization during summer at semiarid region - BHADAURIA, K K S; PAILAN, G H; KUNDU, S S; DAS, M M; LODHI, G N; VERMA, N C (The Indian Journal of Animal Sciences, 2014)
Thirty local female goats available in Bundelkhand region grazed under 2 paddocks @ 1.0 ACU/ha (paddock A) and 2.0 ACU/ha (paddock A) and 2.0 ACU/ha (paddock B) in a shrub omfested grass;amd were se;ected. To nullify the effect of stocking rates half of the goats from each paddock were spplemented with crushed barley grain (group 1) and remaining animals were supplemented concertrate mixture (group 2) during April to July. The goats under both the paddocks primarily selected 6 species ofÂ shrun and less (3.42-7.76% of total forages) quantity of grasses. Digestibility of nutrients was similar in both the grops. N intake/kg DOM intake ws higher (P<0.05) in group 2 than in group 1, however other nutrients intake were similar in both the groups. DCP and ME intkae in both the groups were sufficient for maintenance. The protein as well as energy availability in grazing goats as calculated using CNCPS model was comparable to the conventional digestibility trial and the model can be used to calculated the nutrient requirement of grazing goats.